Cleavage of a pathogen apoplastic protein by plant subtilases activates host immunity. Issue 6 (6th January 2021) - Wang, Shuaishuai; Xing, Rongkang; Wang, Yan; Shu, Haidong; Fu, Shenggui; Huang, Jie; Paulus, Judith K.; Schuster, Mariana; Saunders, Diane G. O.; Win, Joe; Vleeshouwers, Vivianne; Wang, Yuanchao; et al.
Summary: The plant apoplast is a harsh environment in which hydrolytic enzymes, especially proteases, accumulate during pathogen infection. However, the defense functions of most apoplastic proteases remain largely elusive. We show here that a newly identified small cysteine‐rich secreted protein PC2 from the potato late blight pathogen Phytophthora infestans induces immunity in Solanum plants only after cleavage by plant apoplastic subtilisin‐like proteases, such as tomato P69B. A minimal 61 amino acid core peptide carrying two key cysteines, conserved widely in most oomycete species, is sufficient for PC2‐induced cell death. Furthermore, we showed that Kazal‐like protease inhibitors, such as EPI1, produced by P. infestans prevent PC2 cleavage and dampen PC2 elicited host immunity. This study reveals that cleavage of pathogen proteins to release immunogenic peptides is an important function of plant apoplastic proteases.